RANKL promotes osteoblastic activity in vascular smooth muscle cells by upregulating endothelial BMP-2 release. (August 2016) - Davenport, Colin; Harper, Emma; Forde, Hannah; Rochfort, Keith D.; Murphy, Ronan P.; Smith, Diarmuid; Cummins, Philip M.
Abstract: Introduction: Receptor activator of nuclear factor kappa beta-ligand (RANKL) is thought to promote vascular calcification (VC) by inducing osteoblastic behaviour in vascular smooth muscle cells (VSMC) in an ill-defined process. The present study assessed whether RANKL affects pro-osteoblastic paracrine signalling between human aortic endothelial cells (HAEC) and human aortic smooth muscle cells (HASMC) using both conditioned media transfer and cell co-culture experimental approaches. Methods and results: For initial experiments (6-well format), HAEC-conditioned media was harvested following 72 h exposure to RANKL, and transferred to reporter HASMCs with/without noggin, an inhibitor of pro-osteoblastic bone morphogenetic protein (BMP) paracrine signalling. In further experiments, HAECs and HASMCs were co-cultured within the CellMax ® Duo, a perfusing bioreactor unit that mimics the flow-mediated co-interaction of these cells within the arterial wall, and RANKL was added to the perfusing media for 72 h. At the conclusion of each experiment markers of osteoblastic activity were measured in HASMCs, including alkaline phosphatase (ALP) activity, mRNA levels of ALP and Runx2, as well as BMP-2 and BMP-4 concentrations. RANKL increased BMP-2 release from HAECs, while exposure of HASMCs to RANKL-treated HAEC-conditioned media induced osteoblastic behaviour in HASMCs, an effect prevented by noggin. Within the CellMax ® Duo bioreactor, the addition of RANKL to the intraluminal HAECs also produced an increase in BMP-2 and increased osteoblastic behaviour within the co-cultured HASMC population. Conclusions: RANKL promotes VC by inducing BMP-2 release from HAECs, which in turn appears to act in a paracrine fashion on the adjacent HASMC population to increase osteoblastic activity.